SUPERVISI KEPALA MADRASAH DALAM MENINGKATKAN MUTU LEMBAGA PENDIDIKAN ISLAM DI MTs DARUL ULUM XVII SANAH LAOK WARU PAMEKASAN - Syafrawi Syafrawi (Universitas Islam Madura, 2018)
The problem that is the subject of the study in this study is the madrasah chief's strategy in implementing supervision to improve the quality of Islamic education, and the factors that influence it. This study uses a qualitative approach, and the instruments used in data collection by researchers include interviews, observation and documentation. The informants from this study are the Heads, Waka, Teachers and Students. The technique used to check the credibility of the data is the extension of the presence of the researcher, in-depth observation, triangulation, detailed description and analysis of negative cases. The results of the study show that the madrasah chief's strategy in implementing supervision to improve the quality of management of Islamic education institutions is to use several methods, which are varied and some of the approaches taken by the head of the madrasah which can then improve the quality of education in this educational institution, then the other is to use an approach individuals, group approaches, educational approaches, religious approaches or religious approaches, fulfillment of school facilities and infrastructure, appreciation of student learning and so on. While the factors that influence the madrasah chief's strategy in implementing supervision to improve the quality of Islamic education institutions are positive factors which include the existence of adequate human resources, student awareness, and also the existence of cooperation between existing education practitioners, complete facilities and infrastructure, then the teacher's creativity in teaching.